HPMCP-Coated Microcapsules Containing the Ctx(Ile21)-Ha Antimicrobial Peptide Reduce the Mortality Rate Caused by Resistant Salmonella Enteritidis in Laying Hens - Cesar Augusto Roque-Borda; Larissa Pires Pereira; Elisabete Aparecida Lopes Guastalli; Nilce Maria Soares; Priscilla Ayleen Bustos Mac-Lean; Douglas D'Alessandro Salgado; Andréia Bagliotti Meneguin; Marlus Chorilli; Eduardo Festozo Vicente (MDPI AG, 2021)
The constant use of synthetic antibiotics as growth promoters can cause bacterial resistance in chicks. Consequently, the use of these drugs has been restricted in different countries. In recent years, antimicrobial peptides have gained relevance due to their minimal capacity for bacterial resistance and does not generate toxic residues that harm the environment and human health. In this study, a Ctx(Ile21)-Ha antimicrobial peptide was employed, due to its previously reported great antimicrobial potential, to evaluate its application effects in laying chicks challenged with Salmonella Enteritidis, resistant to nalidixic acid and spectinomycin. For this, Ctx(Ile21)-Ha was synthesized, microencapsulated and coated with hypromellose phthalate (HPMCP) to be released in the intestine. Two different doses (20 and 40 mg of Ctx(Ile21)-Ha per kg of isoproteic and isoenergetic poultry feed) were included in the chick's food and administered for 28 days. Antimicrobial activity, effect and response as treatment were evaluated. Statistical results were analyzed in detail and indicate that the formulated Ctx(Ile21)-Ha peptide had a positive and significant effect in relation to the reduction of chick mortality in the first days of life. However, there was moderate evidence (p = 0.07), not considered statistically significant, in the differences in laying chick weight between the control and microencapsulation treatment groups as a function of time. Therefore, the microencapsulated Ctx(Ile21)-Ha antimicrobial peptide can be an interesting and promising option in the substitution of conventional antibiotics.